2016
DOI: 10.5812/ijp.3768
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces Boulardii in Helicobacter Pylori Eradication in Children: A Randomized Trial From Iran

Abstract: Background:Helicobacter pylori infects around 50% of the human population and is asymptomatic in 70% of the cases. H. pylori eradication in childhood will not only result in peptic symptoms relief, but will also prevent late-term complications such as cancer. Today, probiotics are being increasingly studied in the treatment of gastrointestinal infections as an alternative or complement to antibiotics.Objectives:In this study we aimed to assess the effect of S. boulardii supplementation on H. pylori eradication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
0
27
1
4
Order By: Relevance
“…Namkin et al . () reported the positive effect of S . boulardii in reducing the colonization of Helicobacter pylori in the human gastrointestinal system.…”
Section: Resultsmentioning
confidence: 94%
“…Namkin et al . () reported the positive effect of S . boulardii in reducing the colonization of Helicobacter pylori in the human gastrointestinal system.…”
Section: Resultsmentioning
confidence: 94%
“…Despite the improvements in H. pylori eradication with adjunct probiotics, the use of probiotics as monotherapy has been shown to reduce bacterial load but not effective in eradicating H. pylori 30,31. Bhatia et al32 discovered that H. pylori growth was inhibited in vitro if L. acidophilius was present.…”
Section: Discussionmentioning
confidence: 99%
“…The eradication rate was improved (moderate quality evidence), but still below desired level. Namkin et al . reported that S. boulardii was not capable of H. pylori eradication in children when given as single therapy.…”
Section: Probioticsmentioning
confidence: 99%